THE URGENCY OF IMPLEMENTING THE SUNSET CLAUSE IN THE FORMATION OF LEGISLATION IN INDONESIA TO PREVENT OVER-REGULATION - Asep Sapsudin (GoAcademica Research dan Publishing, 2023)
This research is motivated by the phenomenon of overregulation in Indonesia, which has triggered hyperregulation, overlapping regulations, sectoral egos, and legal uncertainty, hampering the national investment climate. Conventional curative regulatory arrangements, such as the omnibus law method, are deemed incapable of addressing the root cause of regulatory overcrowding from the upstream. This research aims to analyze the urgency and formulate an ideal mechanism for institutionalizing sunset clauses (automatic expiration clauses) as a preventative solution to regulatory overcrowding. The research method used is normative juridical with a statute approach and a conceptual approach. Secondary data obtained through literature review was analyzed qualitatively and deductively. The results indicate that the adoption of sunset clauses is urgently needed in the Indonesian legislative system to automatically eliminate